Impact of Bracing on Large Format Prismatic Lithium‐Ion Battery Cells during Aging (Adv. Energy Mater. 10/2022). Issue 10 (10th March 2022) - Daubinger, Philip; Schelter, Matthias; Petersohn, Ronny; Nagler, Felix; Hartmann, Sarah; Herrmann, Matthias; Giffin, Guinevere A.
Abstract : Li‐Ion Batteries In article number 2102448, Guinevere A. Giffin, and co‐workers demonstrate the new concept of mechanical state‐of‐health to describe the positive effect of external bracing on the performance of automotive lithium‐ion cells. This new concept correlates electrode degradation with mechanical effects and shows that external bracing does not affect anode and cathode aging in the same way.